Stratigraphic sequences of Martian erosion features - Jaumann, R.; Reiss, D.; Gasselt, S. van (2003)
Erosion on Mars exhibit a wide variation of fluviatile, periglacial, glacial and eolian surface features. Valley networks, outflow channels, fretted terrain, polygons, thumbprint terrain, thermokarst, eskers, and pingos are the relicts of water and ice driven erosional processes. Based on MOLA and MOC data we examined the morphometric parameters of these features, their areal distribution and their relative age based on superposition and intersection relations and crater densities. In general erosional features are related to each other: valley networks drain into regional depressions from which in most chases large outflow channels originate from chaotic terrain or faults while periglacial and glacial surface features are concentrated at the termination of outflow channels. In other regions valley formation is correlated to the erosion of the highland lowland boundary or glacial features are found in the source regions of south polar valleys. The stratigraphic positions of erosional features also show a general sequence. Valley networks are the oldest features followed by outflow channels and periglacial and glacial landforms are the youngest. Both the areal and temporal distribution of erosional features indicate a constant decrease of erosion processes, which may be related to geological changes like internal cooling rather than to climate changes. Subsurface cycling of H2O is the most plausible mechanism to explain the observed erosion features.